Determinants of Malaria Incidence among Mine Workers: The Role of Length of Stay and Risk Perception - Rezha Rafsanjani Lakoro; Solang Margaretha; Irwan (Ficco Scientific Corner, 2025)
Background: Prolonged duration of stay in mining areas increases exposure to malaria vectors, thereby elevating the risk of transmission. Additionally, workers' perceptions of malaria risk influence their engagement in preventive behaviors, such as using mosquito nets, applying repellents, and avoiding outdoor activities at night. This study analyzes the relationships between the length of stay in mining areas and risk perception, and between the incidence of malaria among mine workers and risk perception. Methods: A quantitative, analytical cross-sectional design was employed. The study population comprised miners in Hulawa Village, Buntulia District, Pohuwato Regency. Key variables included the habit of going out at night and risk perception. Data were collected using a questionnaire, with total sampling. Data analysis utilized the Chi-Square test and Multiple Logistic Regression. Results: There was a significant association between duration of stay in the mining area (ρ value = 0.00; OR = 31.179) and risk perception (ρ value = 0.03; OR = 8.916) with the incidence of malaria among mine workers. Conclusion: The findings indicate a relationship between the duration of stay in mining areas and risk perception, and the incidence of malaria among mine workers.